Prediction of moment of inertia of rotating nuclei - Abu El Sheikh, Mohd Kh. M.; Okhunov, Abdurahim; Abu Kassim, Hasan; U. Khandaker, Mayeen (IOP Publishing on behalf of the Chinese Physical Society (China), 2020)
In this study, the mathematical expression formulated by Bohr for the moment of inertia of even-even nuclei based on the hydrodynamical model is modified. The modification pertains to the kinetic energy of the surface oscillations, including the second and third terms of the R-expansion as well as the first term, which had already been modified by Bohr. Therefore, this work can be considered a continuation and support of Bohr's hydrodynamic model. The procedure yields a Bohr formula to be multiplied by a factor that depends on the deformation parameter. Bohr's (modified) formula is examined by applying it on axially symmetric even-even nuclei with atomic masses ranging between 150 and 190 as well as on some triaxial symmetry nuclei. In this paper, the modification of Bohr's formula is discussed, including information about the stability of this modification and the second and third terms of the R-expansion in Bohr's formula. The results of the calculation are compared with the experimental data and Bohr's results recorded earlier. The results obtained are in good agreement with experimental data, with a ratio of approximately 0.7, and are better than those of the unmodified ones.